Delineation and Characterization of Waterlogged Salt Affected Soils in Loonkaransar Area of IGNP for Reclamation and Management - Mandal, A K; Sharma, R C (Annals of Arid Zone, 2016)
The Indian Remote Sensing (IRS LISS II) data on 1:50,000 scale showed prominent waterlogging as surface ponding in sandy flats and depressions along the Loonkaransar lift canal under the Indira Gandhi Nahar Pariyojona (IGNP). The seasonal data revealed higher extent of waterlogging in February and mixed spectral signatures of high moisture content with poor crop stand in November and permanent waterlogging (close to the lift canal) in June data. Ground truth survey revealed the presence of shallow aquifer (water table depth